Pengaruh Komunikasi Efektif Melalui Pendekatan Bermain Anak Usia 5-6 Tahun - Nurul Aini MM Sodik; Safira Darmayanti; Sri Putri Enjelita; Fibrianti Lastuan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Communication is an important aspect in the development of children aged 5–6 years, especially in supporting their language and social-emotional abilities. This study aims to analyze the influence of effective communication through a play approach in early childhood based on the results of previous research. The method used in this study is a quantitative method by conducting observations, research, and observations on effective communication and a play approach in early childhood education. Data collection techniques were carried out through documentation and literature searches from journals, articles, and relevant scientific references. Data analysis techniques used quantitative descriptive analysis by comparing and summarizing the results of previous research. The results show that the play approach has a significant influence on improving children's effective communication skills, such as the courage to speak, the ability to express opinions, social interaction, cooperation, and self-confidence. In addition, play activities have been proven to be able to create a fun learning atmosphere so that children are more active in interacting with peers and teachers. Thus, the play approach can be an effective strategy in developing the communication skills of children aged 5–6 years.